2023
DOI: 10.1186/s12958-023-01134-1
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy, a critical element in the aging male reproductive disorders and prostate cancer: a therapeutic point of view

Pourya Raee,
Shing Cheng Tan,
Sajad Najafi
et al.

Abstract: Autophagy is a highly conserved, lysosome-dependent biological mechanism involved in the degradation and recycling of cellular components. There is growing evidence that autophagy is related to male reproductive biology, particularly spermatogenic and endocrinologic processes closely associated with male sexual and reproductive health. In recent decades, problems such as decreasing sperm count, erectile dysfunction, and infertility have worsened. In addition, reproductive health is closely related to overall h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 227 publications
0
3
0
Order By: Relevance
“…Furthermore, autophagy's role in the epididymis is receiving study because it may infl uence sperm maturation and storage. Further research into the molecular processes that drive autophagy in these reproductive organs is required for a complete knowledge of its impact on male reproductive physiology [14,54,55]. While the present literature emphasizes the possible role of autophagy in male reproduction, signifi cant knowledge gaps and areas for further investigation remain.…”
Section: Autophagy Agonists and Antagonists Exacerbate Cellular Defectsmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, autophagy's role in the epididymis is receiving study because it may infl uence sperm maturation and storage. Further research into the molecular processes that drive autophagy in these reproductive organs is required for a complete knowledge of its impact on male reproductive physiology [14,54,55]. While the present literature emphasizes the possible role of autophagy in male reproduction, signifi cant knowledge gaps and areas for further investigation remain.…”
Section: Autophagy Agonists and Antagonists Exacerbate Cellular Defectsmentioning
confidence: 97%
“…Despite these intriguing correlations, much about autophagy's potential role in the male reproductive system remains unknown. Understanding the molecular processes and signaling pathways that drive autophagy in male reproductive cells is critical for understanding its impact on fertility, sperm quality, and responses to diverse stresses [13,14]. This review will delve into the available literature, offering a detailed overview of autophagy's possible signifi cance in male reproductive biology as well as emphasizing future research opportunities in this quickly expanding question.…”
Section: Introductionmentioning
confidence: 99%
“…CP can cause reproductive disorders by inducing toxicity in reproductive organs. [ 9 ] This drug can cause tissue changes in the structure of the testis, oxidative stress, fat peroxidation, and DNA damage, and also cause disturbances in gonadotropin secretion, decrease serum testosterone, and thus can harm fertility. [ 10 ] Animal studies have shown that CP leads to decreased testicular weight and transient oligospermia.…”
Section: Introductionmentioning
confidence: 99%